Evaluation of global distribution, genetic evolution, and mammalian infectivity and pathogenicity of H13 and H16 avian influenza viruses - Xiang Li1; Ao Li; Fengyi Qu; Yi Li; Fangyuan Chen; Xinru Lv; Qing An; Mengdan Fei; Hongyu Chen; Hongrui Liang; Xiaotian Zhang; Jinghao Li; et al. (Emerging Microbes and Infections)
H13 and H16 subtype avian influenza viruses (AIVs) typically infect Charadriiformes, are widely distributed throughout coastal regions worldwide, and pose a risk of spill-over to mammals. Systematic research on the epidemiology, transmission dynamics, and biological characteristics of these subtypes remains limited. To address this gap, we analyzed 20 years of wild bird influenza surveillance data from China integrated with global influenza database information to reconstruct the global spatiotemporal distribution, transmission dynamics and public health implications of H13 and H16. During influenza surveillance, 28 H13 and 19 H16 viruses were isolated. The phylogenetic trees for the H13 and H16 viruses revealed that both subtypes could be classified into three distinct groups. Viruses from H13 Group A, H13 Group C, and H16 Group C demonstrated frequent genetic exchanges and intercontinental transmission on a global scale. Mapping host migration revealed overlap between virus spread and host migration pathways. Our results suggest that host migration is a key driver of widespread distribution, cross-regional spread, and gene exchange for some H13 and H16 lineages. Virus isolates exhibit high genetic diversity with rich genotypic variation. Most isolates carry mammalian-adaptive mutations, such as the G228S mutation in the HA protein. H13 and H16 isolates of multiple genotypes infected mice without prior adaptation and exhibited varying tissue tropism. In summary, these findings indicate that host migration patterns are closely associated with the evolution of H13 and H16 AIVs. The potential risk of mammalian infection is highlighted, as viruses carrying mammalian-adaptive mutations may lead to new infection cases.